Promised land of heavy metal : an ethnographical study of the international presence within the metal scene in Finland - Solomon, Serena (My University, 2019)
In this thesis, mainly through ethnographic research and participant observation, I look at the presence of international metal music fans in Finland. My main research question asks first how observable the international presence within the metal scene in Finland is, and then how it has affected the scene. I conducted research through participant observation and ethnographic fieldwork while attending metal music festivals in addition to my role as a music journalist and photographer. I was also able to include observations and ethnographic research through my involvement within the Turku-based metal scene including the Turku University's metal club and other Turku-based events and promotional agencies. I also included interviews that illuminated the perspective of people such as promoters, musicians, patrons and other industry members who were active within the metal scene in Finland. The research concludes that there is an observable international presence within the metal scene in Finland including both visitors and those who have moved to Finland from abroad. The research also concludes that the international presence has had a significant impact on the metal scene in Finland. Examples include my observance of festivals and promotional agencies becoming more accommodating to people coming from abroad or acknowledging the population of non-Finnish patrons by providing more information in English as well as other social media based instances where the international presence was acknowledged such as polls and surveys asking where people are coming from.
Keywords: metal studies, Finland, Finnish metal, metal from Finland, festivals, international, scene, translocal, local, virtual, fandom, fan culture, tourism, ethnography, participant observation, self-reflexivity, phenomenology.